Optical control of cardiac electrophysiology by the photochromic ligand azobupivacaine 2 - Fehrentz, Timm; Amin, Ehsan; Görldt, Nicole; Strasdeit, Tobias; Moussavi-Torshizi, Seyed-Erfan; Leippe, Philipp; Trauner, Dirk; Meyer, Christian; Frey, Norbert; Sasse, Philipp; Klöcker, Nikolaj (British journal of pharmacology, 2025)
Background and Purpose Patients suffering from ischaemic heart disease and heart failure are at high risk of recurrent ventricular arrhythmias (VAs), eventually leading to sudden cardiac death. While high-voltage shocks delivered by an implantable defibrillator may prevent sudden cardiac death, these interventions themselves impair quality of life and raise both morbidity and mortality, which accentuates the need for developing novel defibrillation techniques. Experimental Approach Photopharmacology allows for reversible control of biological processes by light. When relying on synthetic and externally applied chromophores, it renders genetic modification of target cells dispensable and may hence be advantageous over optogenetic approaches. Here, the photochromic ligand azobupivacaine 2 (AB2) was probed as a modulator of cardiac electrophysiology in an ex vivo intact mouse heart model. Key Results By reversibly blocking voltage-gated Na+ and K+ channels, photoswitching of AB2 modulated both the ventricular effective refractory period and the conduction velocity in native heart tissue. Moreover, photoswitching of AB2 was able to convert VA into sinus rhythm. Conclusion and Implications The present study provides the first proof of concept that AB2 enables gradual control of cardiac electrophysiology by light. AB2 may hence open the door to the development of an optical defibrillator based on photopharmacology.
Online verfügbar: 14. November 2024
Gesehen am 26.05.2025